Elimination of congenital rubella: a seroprevalence study of pregnant women and women of childbearing age in Italy - Serena Marchi; Simonetta Viviani; Emanuele Montomoli; Claudia Maria Trombetta (Taylor & Francis Group, 2020)
Prevention of congenital rubella is achieved by vaccination of susceptible women of childbearing age. In Italy, the National Plan for Measles and Congenital Rubella Elimination 2010-2015 implemented catch-up vaccination activities targeting susceptible adolescents and young adults, including women of childbearing age. The aim of this study was to assess the immunity against rubella in women of childbearing age in Tuscany (Central Italy) and Apulia (Southern Italy) and pregnant women in Apulia after the implementation of the National Plan for Measles and Congenital Rubella Elimination. Overall, anti-rubella IgG prevalence in women of childbearing age samples was 88.6% in Tuscany and 84.3% in Apulia. The lowest prevalence was observed in samples of 26-35 years old women of childbearing age in Apulia with 77.8%. Only 62.7% of samples from 26-35 years old pregnant women had IgG against rubella, and one sample out of 95 was positive to IgM. The findings of this study highlight the need for increasing awareness on the risk of contracting rubella infection during pregnancy and implement vaccination strategies to create opportunities for administration of rubella containing vaccines in young girls and women of childbearing age.